On the formation of dwarf galaxies and stellar haloes - Read, J; Pontzen, A; Viel, M (2006)
Using analytic arguments and a suite of very high resolution (∼103 M ⊙ per particle) cosmological hydrodynamical simulations, we argue that high-redshift, z ∼ 10, M ∼ 10 8 M ⊙ haloes, form the smallest 'baryonic building block' (BBB) for galaxy formation. These haloes are just massive enough to efficiently form stars through atomic line cooling and to hold on to their gas in the presence of supernova (SN) winds and reionization. These combined effects, in particular that of the SN feedback, create a sharp transition: over the mass range 3-10 × 10 7 M ⊙, the BBBs drop two orders of magnitude in stellar mass. Below ∼2 × 10 7 M ⊙, galaxies will be dark with almost no stars and no gas. Above this scale is the smallest unit of galaxy formation: the BBB. We show that the BBBs have stellar distributions which are spheroidal, of low rotational velocity, old and metal poor: they resemble the dwarf spheroidal galaxies (dSphs) of the Local Group (LG). Unlike the LG dSphs, however, they contain significant gas fractions. We connect these high-redshift BBBs to the smallest dwarf galaxies observed at z = 0 using linear theory. A small fraction (~100) of these gas-rich BBBs at high redshift fall in to a galaxy the size of the Milky Way (MW). We suggest that 10 per cent of these survive to become the observed LG dwarf galaxies at the present epoch. This is consistent with recent numerical estimates. Those infalling haloes on benign orbits which keep them far away from the MW or Andromeda manage to retain their gas and slowly form stars - these become the smallest dwarf irregular galaxies; those on more severe orbits lose their gas faster than they can form stars and become the dwarf spheroidals. The remaining 90 per cent of the BBBs will be accreted. We show that this gives a metallicity and total stellar mass consistent with the MW old stellar halo. © 2006 RAS.